Communications Between the Endoplasmic Reticulum and Other Organelles During Abiotic Stress Response in Plants - Liu, Linchuan; Li, Jianming (Frontiers in Plant Science, 2019)
To adapt constantly changing environmental conditions, plants have evolved sophisticated tolerance mechanisms to integrate various stress signals and to coordinate plant growth and development. It is well known that interorganellar communications play important roles in maintaining cellular homoeostasis in response to environmental stresses. The endoplasmic reticulum (ER), extending throughout the cytoplasm of eukaryotic cells, is a central organelle involved in lipid metabolism, Ca2+ homeostasis, and synthesis and folding of secretory and transmembrane proteins crucial to perceive and transduce environmental signals. The ER communicates with the nucleus via the highly conserved unfolded protein response pathway to mitigate ER stress. Importantly, recent studies have revealed that the dynamic ER network physically interacts with other intracellular organelles and endomembrane compartments, such as the Golgi, mitochondria, chloroplast, vacuole, and the plasma membrane, through multiple membrane contact sites between closely apposed organelles. In this review, we will discuss the signaling and metabolite exchanges between the ER and other organelles during abiotic stress responses in plants.